2008
DOI: 10.1007/s10484-008-9050-5
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic (EEG) Measurements of Mindfulness-based Triarchic Body-pathway Relaxation Technique: A Pilot Study

Abstract: These results provided evidence to support that the TBRT gives rise to positive emotional experience, accompanied by focused internalized attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 51 publications
3
43
2
Order By: Relevance
“…In contrast, a negative score denoting greater alpha power on the left and less alpha power on the right represents relatively greater activation on the right side, suggesting a more negative emotional response. Our empirical and clinical studies [9092] have shown that frontal alpha asymmetry provides an effective and reliable means of distinguishing between positive and negative emotions. Greater left-sided activation is also associated with reduced anxiety and feelings of well-being [9094, 98, 100].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a negative score denoting greater alpha power on the left and less alpha power on the right represents relatively greater activation on the right side, suggesting a more negative emotional response. Our empirical and clinical studies [9092] have shown that frontal alpha asymmetry provides an effective and reliable means of distinguishing between positive and negative emotions. Greater left-sided activation is also associated with reduced anxiety and feelings of well-being [9094, 98, 100].…”
Section: Introductionmentioning
confidence: 99%
“…Our empirical and clinical studies [9092] have shown that frontal alpha asymmetry provides an effective and reliable means of distinguishing between positive and negative emotions. Greater left-sided activation is also associated with reduced anxiety and feelings of well-being [9094, 98, 100]. Therefore, if microcurrent stimulation at the Shenmen acupoint leads to an improvement in mood, a change in brain activity measured by frontal alpha asymmetry may be observed after stimulation and the reduction in absolute alpha power should be more prominent in the left frontal region, as compared to the frontal region in the right hemisphere, resulting in a positive frontal alpha asymmetry score after stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in frontal alpha/theta activity are demonstrated by experienced Zen meditators (66). Studies of meditation-induced relaxation have demonstrated an increase in frontal midline theta (4-8 Hz) activity compared with subjects relaxing while listening to music (67). Increased frontal theta and posterior alpha are apparently characteristic of unfocused meditative techniques (68).…”
Section: Meditative Statesmentioning
confidence: 99%
“…13,14 Differences were calculated for electrode pairs in frontal and prefrontal regions (AF3-AF4, AF7-AF8, F1-F2, F3-F4, F5-F6, and F7-F8), then averaged across sites to increase the signal:noise ratio. 34 The AAI reflects an inverse relationship between EEG power and alpha desynchronization due to out-of-phase wave cancellation resulting from activation of independently oscillating neural units.…”
Section: Asymmetric Activationmentioning
confidence: 99%
“…10,11 Left-anterior activation, as evidenced by alpha desynchronization and a corresponding decrease in EEG alpha power relative to the opposite hemisphere, is also known to increase with mindfulness meditation, [12][13][14][15][16] and to be correlated with improved immune function, increased vitality, approach-oriented motivation, and general well-being; right-anterior activation, the reverse. 9,[17][18][19] Moreover, individuals with greater left-anterior activation recover more quickly from exposure to negative stimulation, suggesting left-anterior activation to be an effective adaptation to stress.…”
mentioning
confidence: 99%